Linguistic features of scientific and technical terms in English and Uzbek languages (Eurasian Research Bulletin, 2024)
In this article, the linguistic features of scientific and technical terms in English and Uzbek, the creation of new terms in Uzbek with the development of scientific and technical fields, the decisive role of scientific and technical terms in conveying specific and special information in various fields are fully described